Low-toxic, fluorescent labeled and size-controlled graphene oxide quantum dots@polystyrene nanospheres as reference material for quantitative determination and in vivo tracing. (November 2022) - Liang, Jie-Ling; Cao, Gong-Xun; Zheng, Feng-Ying; Li, Shun-Xing; Liu, Feng-Jiao; Lin, Lu-Xiu; Huang, Xu-Guang; Zhang, Zi-Huan; Zheng, Jing-Yin; Huang, Qian-Yan
Abstract: Polystyrene (PS) is selected as a representative nanoplastic and persistent pollutant for its difficult degradation and wide application. The environmental risk assessment of PS is obstructed by the toxic dye-based fluorescent PS, which false positives could be induced by the leakage of dye. For high biocompatibility, low toxicity, hydrophilicity, good water dispersibility, strong fluorescent stability, graphene oxide quantum dots ( o -CQDs) are selected and embedded into PS microspheres, i.e., o -CQDs@PS, by microemulsion polymerization and denoted as CPS. Meanwhile, the sizes of CPS, e.g., 100, 150, and 200 nm, could be controlled by optimizing the type and number of water-soluble initiators. The anti-interference, low toxicity, and in vivo fluorescent tracing of CPS are proven by the coexistence of metals (including Fe 2+, Fe 3+, K +, Ba 2+, Al 3+, Zn 2+, Mg 2+, Ca 2+, and Na + ) on the fluorescence intensity of CPS, the growth of Chlorella pyrenoidosa and Artemia cysts as aquatic phytoplankton and zooplankton cultured with CPS, and the transfer of CPS from water into brine shrimp. In the concentration range of 0.1–100 mg/L, CPS can be quantitatively determined, which is suitable for coastal water and wastewater treatment plants. Therefore, CPS with standard size is suitable as reference material of PS. Graphical abstract: Image 1 Highlights: For biocompatibility, low toxicity and fluorescent stability, o -CQDs are used. Size-controlled o -CQDs@PS (CPS) can be used as reference material. CPS is used for in vivo fluorescence tracing of PS intake. CPS in coastal and waste water can be detected quantitatively.